Performance, Environmental, and Mobility Analysis of Large Capacity Fast Rotorcraft Configurations for the European Regional Air Traffic Market - Declerck, L.M.A.; Cruellas Bordes, M.; Saias, C.A.; Nalianda, D.; Schreiner, B.D.J.; Misté, G.A.; Dal Monte, A.; Benini, E.; Junior, A. (My University, 2023)
Fast, large rotorcraft are of interest in the future European air transport system due to their runway independent operation and potential mobility improvements for the passenger. Both a tiltrotor and a coaxial compound concept model were developed for a 70 passenger, 500 NM design mission that would compete with regional fixed-wing aircraft. These models were flown along virtual trajectories representing possible use-cases and assessed for environmental performance in comparison to an in-service baseline aircraft using comparable engine technology levels. Further, the travel time and mobility improvement available to the intermodal transport network through the inclusion of these concept rotorcraft was examined with promising results. Future work is suggested to address the shortfall in environmental performance.